Sovereign credit risk and exchange rates: Evidence from CDS quanto spreads - Augustin, Patrick; Chernov, Mikhail; Song, Dongho (Journal of Financial Economics, 2020)
Sovereign credit default swap quanto spreads tell us how financial markets view the interaction between a country’s likelihood of default and associated currency devaluations (the Twin Ds). A no-arbitrage model applied to the term structure of eurozone quanto spreads can isolate the Twin Ds and can gauge the associated risk premiums. Conditional on the occurrence of default, the true and risk-adjusted one-week probabilities of devaluation are 42% (2%) and 90% (55%) for the core (periphery) countries. The weekly risk premium for euro devaluation in case of default for the core (periphery) exceeds the regular currency premium by up to 18 (13) basis points.